Biomedical issues in Islamic family law - Haneef, Sayed Sikandar Shah (Thinker`s Library Sdn. Bhd., 2015)
Islamic discourse on biomedical issues is one of the most topical themes in contemporarylslamicthought.However,literatureespousingthissubject demonstrates dichtomo, up"p.ou.hes by treating issues either from ethcical point ofvieworlegaiperspective'Mo,.o*.,thediversityofjuristicpronouncements containing views f.ri upf...iative of the larger ethical impiications of medical technology on core f;ily value-system as Jnvisioned by Islam proves confusing to common folk and paradoxical to research scholars' To remedy the situation' thisbookarguesforanintegratedapproachbybringingtogethertheimmutable principles of rsta*ic?amiryiu* u, ..,ihrir-,.d in the Qur'an and the Strnnah i""g *iat the underlying moral purposes of the law on marriage, procreation, p""i"ny arrd medicj.uL' ettoidingly' it proposes that to thwart the ethico-juridical pitfalls on medical management of family issues, singular reliance on scientihc e"perts may not be adequate. The_ experts specializing in this area should ,fr" ".q""int themselves witil the working knowledge of medical ie.hrrotogies and relatei disciplines. This approach *:r1+ facilitate the accommodation of biomedical technologies into the legal parameters of Islamic family iaw in a more ethically consistent articulation u'hich could be reassuring to ordinary folks and technically coherent to reserchers in the field'